2012
DOI: 10.5194/hess-16-1623-2012
|View full text |Cite
|
Sign up to set email alerts
|

Satellite remote sensing of water turbidity in Alqueva reservoir and implications on lake modelling

Abstract: Abstract. The quality control and monitoring of surface freshwaters is crucial, since some of these water masses constitute essential renewable water resources for a variety of purposes. In addition, changes in the surface water composition may affect the physical properties of lake water, such as temperature, which in turn may impact the interactions of the water surface with the lower atmosphere.The use of satellite remote sensing to estimate the water turbidity of Alqueva reservoir, located in the south of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 25 publications
3
44
0
2
Order By: Relevance
“…This is because the lower layers in dark waters accumulate less heat during the heating season as opposed to clear waters, which results in less heat storage and lower water column temperature in dark waters (Heiskanen et al, 2015;Potes et al, 2012). The MWCT decreased by 0.94 • C (increased by 0.63 • C) when maximum (minimum) K d value was used instead of its average value during the study period.…”
Section: Sensitivity Of Flake To K D Variationsmentioning
confidence: 97%
See 3 more Smart Citations
“…This is because the lower layers in dark waters accumulate less heat during the heating season as opposed to clear waters, which results in less heat storage and lower water column temperature in dark waters (Heiskanen et al, 2015;Potes et al, 2012). The MWCT decreased by 0.94 • C (increased by 0.63 • C) when maximum (minimum) K d value was used instead of its average value during the study period.…”
Section: Sensitivity Of Flake To K D Variationsmentioning
confidence: 97%
“…Their results showed that water clarity is an essential parameter affecting the simulated LSWT. The daily mean LSWT increased from 1.2 • C in clear water to 2.4 • C in dark water (Potes et al, 2012). Water clarity measurements are included in water quality monitoring programs; however, global measurements of clarity are not yet available.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reflectance in this spectral region increases towards the maximum at 565 nm. Potes et al (2012) showed a high correlation (0.96) between the water-leaving reflectance ratio 560Á412.5 nm and water turbidity for the Alqueva reservoir. The scatter plot for the ratio at or near the wavelengths of Potes et al (2012) was performed and presented a lower correlation with respect to the one presented here.…”
Section: Evaluation Of the Lake Modelmentioning
confidence: 99%